Students Can Purposefully Create Information, Not Just Consume It. Issue 3 (4th October 2014) - Lapp, Diane; Fisher, Douglas; Frey, Nancy; Gonzalez, Alex
Abstract Social media has become adolescents' primary platform for communicating with one another. As a school faculty we wanted to explore our students' ability to contribute new information while being sensitive not to co‐opt their out of school literacies for school‐based purposes.This article shares how teachers in one urban school redesigned curriculum and instruction to provide experiences that encourgaed and supported students as they engaged in the production side of social media.